Fisetin and/or capecitabine causes changes in apoptosis pathways in capecitabine-resistant colorectal cancer cell lines - CABADAK, HÜLYA (My University, 2024)
Capecitabine is recommended as one of the first-line chemotherapy treatments for advanced or metastatic colorectal cancer. Researches have been conducted on capecitabine’s impact on the viability of human colon cancer cells and its potential to induce apoptosis. However, even in cases initially responsive to treatment, the development of acquired resistance significantly limits its efficacy. Challenges still exist in effectively treating patients with chemotherapy, and developing new cytotoxic drugs is hindered by drug resistance. Fisetin alters the cell cycle, inducing apoptosis, inhibiting cancer cell proliferation, and enhancing the therapeutic effectiveness of chemotherapy drugs. This work aims to create a plan for reversing capecitabine resistance. For this purpose, the role of capecitabine and/or fisetin combinations in cell proliferation and apoptosis has been determined in both wild-type and capecitabine-resistant HT29 cells (CR/HT29). We developed capecitabine-resistant cell line from wild-type HT29 cells. This study demonstrated the effects of capecitabine, fisetin, and their combinations on both resistant and wild-type cells through experiments including cell survival skills, cell proliferation, wound healing, colony formation, hoechst staining, and western blot analysis. We established capecitabine-resistant cell lines. P-gp expression increased in CR/HT29 cells. Capecitabine effects on a CR/HT29 cells less than wild-type HT29 cells. The combination of fisetin and capecitabine in cell proliferation caused greater reductions in wild-type HT29 cells than in capecitabine-resistant cells. Fisetin has also additive effects on the apoptotic pathway in CR/HT29 cells. This study provides new perspectives on the combination of capecitabine and/or flavonoid treatment in resistant cells. Graphical abstract: (Figure presented.)
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); Farmakoloji ve Toksikoloji; FARMAKOLOJİ VE ECZACILIK; Life Sciences (LIFE); PHARMACOLOGY & TOXICOLOGY; PHARMACOLOGY & PHARMACY; Farmakoloji; Pharmacology; Apoptosis; Capecitabine-resistance; Fisetin; HT29 cell; Wound-healing